Hyaluronic acid layered chimeric nanoparticles: targeting MAPK-P13K signaling hub in colon cancer cells - Palvai, Sandeep; Kuman, Meenu Mahesh; Sengupta, Poulonu; Basu, Sudipta (ACS Omega, 2017)
Colon cancer has emerged as one of the most devastating diseases in the whole world. Mitogen-activated protein kinase (MAPK)-phosphatidylinsitol-3-kinase (PI3K) signaling hub has gained lots of attention due to its deregulation in colon cancer cells. However, selective targeting of oncogenic MAPK-PI3K hub in colon cancer has remained highly challenging, hence it has mostly been unexplored. To address this, we have engineered a hyaluronic acid layered lipid-based chimeric nanoparticle (HA-CNP) consisting of AZD6244 (MAPK inhibitor), PI103 (PI3K inhibitor), and cisplatin (DNA impairing drug) ratiometrically in a single particle. Electron microscopy (field emission scanning electron microscopy and atomic force microscopy) and dynamic light scattering were utilized to characterize the size, shape, morphology, and surface charge of the HA-CNPs. Fluorescent confocal laser scanning microscopy and flow cytometry analysis confirmed that HA-CNPs were taken up by HCT-116 colon cancer cells by merging of clathrin and CD44 receptor-mediated endocytosis along with macropinocytosis to home into acidic organelles (lysosomes) within 1 h. A gel electrophoresis study evidently established that HA-CNPs simultaneously inhibited MAPK-PI3K signaling hub with DNA damage in HCT-116 cells. These HA-CNPs stalled the cell cycle into G0/G1 phase, leading to induction of apoptosis (early and late) in colon cancer cells. Finally, these HA-CNPs exerted remarkable cytotoxicity in HCT-116 colon cancer cells at 24 h compared to that of the free triple drug cocktail as well as HA-coated dual drug-loaded nanoparticles without showing any cell death in healthy L929 fibroblast cells. These HA-coated CNPs have potential to be translated into clinics as a novel platform to perturb various oncogenic signaling hubs concomitantly toward next-generation targeted colon cancer therapy.